Design, development and randomised controlled trial protocol of a smartphone-delivered version of ‘SOLAR’ for emergency service workers to manage stress and trauma - Meaghan O'Donnell; Olivia Metcalf; Kari Gibson; Julia Fredrickson; Laura Finlayson-Short; Tracey Varker (BMJ Open, 2023)
Methods and analyses First, focus groups and codesign activities with mental health professionals and emergency service workers will be conducted to develop and test the prototype smartphone version of SOLAR (ie, SOLAR-m). Second, a multicentre randomised controlled trial will investigate the effectiveness of the new app, compared with an active control app, in reducing symptoms of anxiety and depression (primary outcome), as well as other indicators of mental health and work performance. Firefighters from one of the largest urban fire and rescue services in Australia who are currently experiencing distress will be invited to participate. After screening and baseline assessment, 240 will be randomised to receive either SOLAR-m or the control app for 5 weeks, with measurements pre, post and 3-month follow-up. Analyses will be conducted within an intention-to-treat framework using mixed modelling.Ethics and dissemination The current trial has received ethics approval from the University of Melbourne Human Research Ethics Committee (2021-20632-18826-5). Study results will be disseminated through peer-reviewed journals and conferences, with a focus on how to expand the new app to other trauma-affected populations if proven effective.Trial registration number ANZCTRN12621001141831.